GUIDE: A GUI for automated quantum chemistry calculations - Sarkar, Arkadeep; Sessa, Lucia; Marrafino, Francesco; Piotto, Stefano (Journal of Computational Chemistry, 2023)
The accuracy of quantum mechanics (QM) simulations depends heavily on the quality of initial input files. Despite the popularity of QM simulation packages, achieving precise results still heavily relies on the user's proficiency in preparing the QM simulation systems. In this work, we present an easy-to-use tool called GUIDE, a YASARA plugin to assist researchers in quantum chemistry workflow automation using ORCA and MOPAC simulation packages. GUIDE lets users compute complex QM calculation workflows via an automated graphical window system. It allows for a more integrated and streamlined research process, as researchers can easily access all the necessary tools within one software without switching between multiple programs. This tool can save time and increase efficiency in computational chemistry methods. GUIDE is written in Python and is freely available for download at . The plugin is released under a GPL-3.0 license and is supported on Windows and Linux.